The Regional Security Challenge in the 21st Century: Maritime Disputes As Implication of Energy Crisis - Hersutanto, Begi (UI Scholars Hub, 2006)
For the last one decade, most of the countries in the Southeast Asia region have shown dramatic growth of economic development. Given the fact that most of the countries in the region currently can be called emerging industrial development progress and the life of the nations. These soon-to-be industrialized countries mostly still rely on oil. Hence, based on the assumption that the source of oil is shrinking while the demand is increasing, in the future these countries will have to struggle to secure the oil source. As the oil sources mostly lie beneath the sea, the competition among the countries for seeking oil will have implications for emerging maritime dispute in the future. In this rivalry over energy between Southeast Asian countries the future stability and security of the region in one way or another depend on the peace peaceful settlement dispute as promoted by a cyan framework the effects of ASEAN members in preserving the values for peaceful settlement dispute will be the key to resolve the energy insecurity conflict.